Effect of Annealed Si/Ti/Pt Hetero Structure on The Response Time and Signals of Hydrogen Sensors - Wahyu Widanarto; Farzand Abdullatif; Christoph Senft; Walter Hansch (Institut Teknologi Bandung, 2011)
Titanium (Ti) and platinum (Pt) films deposited on p-doped Si electrode were incorporated as gas sensitive electrodes in Kelvin and Floating Gate Field Effect Transistor (FG-FET) systems. The films were annealed in oxygen at 800°C. SEM and EDX characterization methods were employed to study the surface of these films. Work function changes with respect to various hydrogen concentrations have been measured as a function of temperature and humidity. The results show that nano grains of titanium silicide (TiSi2) and Pt islands are formed after the annealing. Annealed TiSi2/Pt films are well suitable to significantly stabilize FG-FET based hydrogen sensor. The sensors can detect H2 in concentration range between 0.3% and 2% from room temperature up to 135°C. The response time is quite fast i.e. t90 43.2 seconds. An experiment on the stability has proved that signal pattern of the sensors remained stable one month after first conditioning.